Perbandingan Dialek Bahasa Melayu Riau antara Desa Pulau Panjang Kecamatan Cerenti dan Desa Lebuh Lurus Kecamatan Inuman Kabupaten Kuantan Singingi - Gustria Harisa, Wina; Tinambunan, Jamilin (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This research aims to understand the similarities, resemblances, and differences between the vocabulary of the Malay language in these two dialects. The approach used in this research is qualitative with data analysis methods. Data collection techniques include observation, interviews, and documentation. The research findings show similarities, resemblances, and differences in the analyzed vocabulary between the two dialects. The implications of this research enrich our understanding of the variation of the Malay language in the Pulau Panjang and Lebuh Lurus dialects in Kuantan Singingi Regency. By understanding the similarities, resemblances, and differences between these dialects, we can better understand the dynamics of language and local culture in the region. The practical implications can be used as a reference for researchers, language instructors, and the general public in understanding and preserving the diversity of regional languages and cultures. Additionally, this research can serve as a foundation for efforts to conserve and develop the Malay language in its local context.